Scientific developments in educational innovation research in Indonesia and Malaysia: a scientometric review - Sofyan, Davi; Abdullah, Khairul Hafezad (Universitas Majalengka, 2022)
Educational innovation, in its early days, aims to improve educational quality. Active and experiential learning, as well as authentic assessment, are examples of educational innovation. The goal of high-impact practices is to make education more intentional, coherent, developmental, and transformative. This paper examines the evolution of educational innovation research conducted globally based on the Scopus and WoS database. The parameters considered in this study embrace the growth of publications, suubject areas, source titles, countries, institutions, author and authors’ keywords. Another intriguing finding concerns the source title; the Journal of Physics: Conference Series leads 18 publications. In addition, this study indicated that Putra A.B.N.R., of the Universitas Negeri Malang in the Indonesia, is the most active author, having published 6 documents. Other databases, such as PubMed and Google Scholar, can be used to obtain more detailed metadata. Our research contributes to future research trends by providing visualisation and cutting-edge knowledge of educational innovation